MeerKAT radio observations of the neutron star low-mass X-ray binary Cen X–4 at low accretion rates. Issue 2 (26th August 2022) - van den Eijnden, J; Fender, R; Miller-Jones, J C A; Russell, T D; Saikia, P; Sivakoff, G R; Carotenuto, F
ABSTRACT: Centaurus X–4 (Cen X–4) is a relatively nearby neutron star low-mass X-ray binary that showed outbursts in 1969 and 1979, but has not shown a full outburst since. Due to its proximity and sustained period of quiescence, it is a prime target to study the coupling between accretion and jet ejection in quiescent neutron star low-mass X-ray binaries. Here, we present four MeerKAT radio observations at 1.3 GHz of Cen X–4, combined with NICER and Swift X-ray monitoring. During the first and most sensitive observation, Cen X–4 was in a fully quiescent X-ray state. The three later and shorter observations targeted a brief period of faint X-ray activity in 2021 January, which has been referred to as a 'mis-fired' outburst. Cen X–4 is not detected in any of the four MeerKAT observations. We place these radio non-detections on the X-ray–radio luminosity diagram, improving the constraints on the correlation between the two luminosities from earlier quiescent radio studies. We confirm that Cen X–4 is radio fainter than the transitional millisecond pulsar PSR J1023+0038 at the same X-ray luminosity. We discuss the radio behaviour of accreting neutron stars at low X-ray luminosity more generally and finally comment on future observing campaigns.